Social Theory of Fear Terror, Torture, and Death in a Post-Capitalist World - Skoll, Geoffrey R. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org. In the current crisis of the capitalist world system, elites promote fear of crime and terrorism to keep and expand their privileges and control the masses. This book offers an analysis of the crisis and strategies for rebellion. This ebook is participating in an experiment and is available Open Access under the Creative Commons Attribution-Non Commercial-No Derivatives 3.0 Unported (CC BY-NC-ND 3.0) licence. Users are free to disseminate and reuse the ebook. The licence does not however permit commercial exploitation or the creation of derivative works without specific permission. To view a copy of this license visit http://creativecommons.org/licenses/by-nc-nd/3.0.